LOGOCENTRISM OF PURITAN IDEA AND ITS TRANSFORMATION IN POSTMODERN ERA: NEAL STEPHENSON’S NOVEL “SNOW CRASH”. - KRYNYTSKA, Nataliya (Alfred Nobel University Journal of Philology / Vìsnik Unìversitetu ìm. A. Nobelâ: Serìâ Fìlologìčnì Nauki, 2024)
The aim of the article is to determine the ways of transforming the logocentrism of the Puritan idea in Neal Stephenson’s post-cyberpunk novel “Snow Crash” (1992). The tasks of this research include: reviewing Puritan sources relating to the Word of God from the point of view of modern language theory; studying the transformation of text into a logos that changes reality in “Snow Crash” and Puritan sermons; displaying the opposition ‘body / mind (soul)’ through language in these sermons and overcoming it in the vir-‘body / mind (soul)’ through language in these sermons and overcoming it in the vir-body / mind (soul)’ through language in these sermons and overcoming it in the virtual reality of the novel; comprehending the Sapir-Whorf hypothesis and combining linguistic determinism with the idea of Puritan logocentrism in “Snow Crash”; studying the implementation of the Tower of Babel motif in the novel; and analysing intertextuality in Stephenson’s work. The main methods of research are cultural-historical, philosophical-aesthetic, hermeneutic, mythopoetic and intertextual analysis. The new findings prove that the Puritans’ focus on the Holy Scriptures as a direct path to divine truth corresponds to the novel’s exploration of language as a powerful tool of control and influence. Adhering to the Holy Scriptures, the Puritan leaders aimed not only at a high spiritual mission but also at a purely pragmatic task of fighting the chaos of an unknown and dangerous world and controlling their flock for the most rational and effective survival in difficult conditions. The author emphasizes that both in the Puritan ideology and in the poetic world of the novel, there is a transformation of writing into speech. This is as if Stephenson is following a puritanical script of using the Present Tense to bring the text to life for the audience and then to change reality with that logos. Parallels have been found between Puritan rhetoric and the achievement of transcendence in Stephenson’s Metaverse. Comparing the Word of God to medicine, food, glass or a trumpet in their sermons, Puritan priests thus activated the sensory perception of their flock, giving ‘flesh’ to an abstract text. The author assumes that they were intended to ‘reprogram’ the believers’ perception of reality with an emphasis on the negative aspects of society. The Metaverse is also a text – a computer protocol, and every year programmers increase its virtual flesh, i.e., its size and diversity by simulation of neural sensory perception. The Puritans and the programmers rely on the text and on the interaction of body and mind/soul through language. However, whereas the Puritans used the text to improve the real world according to their views, the programmers created a new virtual world. The Metaverse is the embodiment of the Puritan dream of a ‘Millennial Paradise’ or ‘City upon a Hill’. On the one hand, this cyberspace is created in search of freedom by hackers to escape from hyper-capitalist reality, but on the other hand, only the richest or those with high technology have access to this form of transcendence. The paper studies “Snow Crash” as an illustration of the ‘strong’ version of the Sapir-Whorf hypothesis, which looks at the dangers of using language as a mental or computer virus where the minds of humans as biorobots are literally reprogrammed. Puritan beliefs were often characterized by moral absolutism and a desire to control social behaviour to conform to religious ideals. The Tower of Babel motif is traced from the point of view of the existence of a single protolanguage, which split into many others after the destruction of the tower by God. In “Snow Crash”, the Los Angeles fragmented reality is as diverse as post-infocalypse Babel, where the protagonist is a virtual frontier cowboy, culture hero and trickster. Stephenson praises the Babel infocalypse, when human language became heterogeneous, understanding it as a moment of liberation and the beginning of the countdown of independent rational thinking of humankind. He also reverently perceives the following of the Bible over the centuries as ‘informational hygiene’ – this is how the people of the ‘Book’ resisted the ancient pagan chaos. The novel’s reinterpretation of the idea of Puritan logocentrism takes place within postmodern aes-’s reinterpretation of the idea of Puritan logocentrism takes place within postmodern aes-s reinterpretation of the idea of Puritan logocentrism takes place within postmodern aesthetics through the use of deconstruction (revaluing the idea of logocentrism and the Tower of Babel myth), parody (debunking the myth of the City upon a Hill), irony and intertextuality. But although “Snow Crash” is ironical, the writer at a deeper level rejects postmodern cynicism and helplessness. The American nation continues to develop, critically reviewing and reforming its founding myths. Adhering to the science fiction faith in science and the Puritan belief in the constructive potential of the word for society, Neal Stephenson created his metanarrative about the Metaverse. This became the prototype of the modern Internet, but, in its full embodiment of an alternative reality, remains a dream and a guide for progressive humanity today.